2013
DOI: 10.1108/ijoa-mar-2012-0574
|View full text |Cite
|
Sign up to set email alerts
|

Perceived organizational support as a moderator in the relationship between organisational stressors and organizational citizenship behaviors

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 66 publications
(85 reference statements)
2
74
0
5
Order By: Relevance
“…In other words, in the highly demanding work context in where employees need to be as engaged as possible towards their work, they expect higher organizational support to maintain their membership within the organization. Jain et al (2013) suggested that employees' outputs are the direct function of the inputs that they receive from their organizations in any social exchange. In fact, the extent of employees' effort in the job is manifested by their feelings of endorsement given by the organizations, which in turn, enhances the level of engagement (Hur et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, in the highly demanding work context in where employees need to be as engaged as possible towards their work, they expect higher organizational support to maintain their membership within the organization. Jain et al (2013) suggested that employees' outputs are the direct function of the inputs that they receive from their organizations in any social exchange. In fact, the extent of employees' effort in the job is manifested by their feelings of endorsement given by the organizations, which in turn, enhances the level of engagement (Hur et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, POS is the social exchange relationship between employer and employee. Scholars identified POS as an important construct since it has the positive impact on the quality relationship of management and employee (Wayne et al, 1997), employee engagement (Nazir & Islam, 2017;Kinnunen, Feldt, & Makikangas, 2008), organizational citizenship behavior (Jain, Giga & Cooper, 2013), organizational commitment (Nazir & Islam, 2017). and has the negative impact on turnover intentions and deviant behavior (Colbert, Mount, Harter, Witt, & Barrick, 2004;Rhoades, Eisenberger, & Armeli, 2001).…”
Section: Moderating Role Of Perceived Organizational Supportmentioning
confidence: 99%
“…This helps employees' input of their time and effort to be relatively safe. It thereby helps employees to input higher job performance, and then beyond the organization's expectations for the reason that they have a hand in more innovative and spontaneous behavior to benefit the organizational [23] Hypothesis 3: POS is positively related to OCB.…”
Section: Hypothesis 2: Soe Moderates the Pss-pos Relationship Such Thmentioning
confidence: 97%
“…According to Awwad & Agti, (2011) without commitment there is no effective performance in which commitment has a significant association with OCB dimensions. Jain, Giga and Cooper, (2012) stated that stress and conflict negatively impact job commitment, OCB and performance. Liu, (2009) stated that employees participating in voluntary helpful behavior such as (altruism, conscientiousness and civic virtue) are considered to be exhibiting affective behavioral responses.…”
Section: Job Commitmentmentioning
confidence: 99%
“…Voluntary turnover intention is viewed as the most detrital as it comes unexpected. High employees turnover rate influences organizational performance as it will eventually inflate the replacement and training costs (Chou & Lopez-Rodriguez, 2013;Jain et al, 2012). However in most cases employees are the ones to freely resign from a job.…”
Section: Turnover Intentionsmentioning
confidence: 99%